SUITABILITY ASSESSMENT OF SOILS IN IFE AREA (Southwestern Nigeria) FOR COFFEE ROBUSTA (Coffea canephora Pierre ex A. Froehner) PRODUCTION - OLASOJI, H. O.; OJETADE, J. O.; AMUSAN, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Land suitability evaluation is imperative to identify appropriate land use for effective productivity. This also helps to ascertain the constraints and opportunities for land use and guides decision-makers in their plans. The objective of this study was to assess the suitability of the soils of the study area for coffee production. A parametric model of a suitability assessment and geographical information system was used for the evaluation exercise. Five soil profile pits were established on a toposequence (upper, middle and lower slope), and soil samples taken from pedogenic horizons were described morphologically on the field; physically and chemically in the laboratory following standard procedures. The results of the study showed that the soils were generally well-drained and deep with no restrictions. Sand content in the surface horizons ranged from 62 to 82%, clay from 8 to 20% and silt from 7 to 14%.  The pH was low (4.4 to 5.9), while organic carbon content ranged from 0.66 to 1.64. Environmental factors and fertility status affecting coffee growth and productivity were moderate. Currently, the land is moderately suitable for coffee robusta production. However, the result of the potential productivity index revealed that the land would be highly suitable if properly managed through the application of appropriate fertilizer.